Building an ecologically-founded disease risk prioritization framework for migratory species based on contact with livestock - Khanyari, Munib; Robinson, Sarah; Morgan, Eric; Brown, Tony; Singh, Navinder; Salemgareyev, Albert; Zuther, Steffen; Kock, Richard; Milner-Gulland, E (Dryad, 2021)
1. Shared use of rangelands by livestock and wildlife can lead to disease
transmission. To align agricultural livelihoods with wildlife
conservation, a multi-pronged and interdisciplinary approach for disease
management is needed, particularly in data-limited situations with
migratory hosts. Migratory wildlife and livestock can range over vast
areas, and opportunities for disease control interventions are limited.
Predictive frameworks are needed which can allow for identification of
potential sites and timings of interventions. 2. We developed an iterative
three-step framework to assess cross-species disease transmission risk
between migrating wildlife and livestock in data-limited circumstances and
across social-ecological scales. The framework first assesses risk of
transmission for potentially important diseases for hosts in a multi-use
landscape. Following this, it uses an epidemiological risk function to
represent transmission-relevant contact patterns, using density and
distribution of the host to map locations and periods of disease risk.
Finally, it takes fine-scale data on livestock management and observed
wildlife-livestock interactions to provide locally-relevant insights on
disease risk. 3. We applied the framework to characterize disease
transmission between livestock and saiga antelopes (Saiga tatarica) in
Central Kazakhstan. 4. At step 1, we identified peste-des-petits-ruminants
as posing a high risk of transmission from livestock to saigas,
foot-and-mouth disease as low risk, lumpy skin disease as unknown and
pasteurellosis as uncertain risk. At step 2 we identified regions of high
disease transmission risk at different times of year, indicating where
disease management should be focussed. At step 3, we synthesized field
surveys, government data and literature review to assess the role of
livestock in the 2015 saiga mass mortality event from pasteurellosis,
concluding that it was minimal. 5. Synthesis and Applications. Our
iterative framework has wide applicability in assessing and predicting
disease spill-over at management-relevant temporal and spatial scales in
areas where livestock share space with migratory species. Our case study
demonstrated the value of combining ecological and social information to
inform management of targeted interventions to reduce disease risk, which
can be used to plan disease surveillance and vaccination programmes.
Keywords: disease transmission; saiga; multi-use landscapes; Overlap; socio-ecological system; uncertainity